Determinación de alteraciones del sistema digestivo alto mediante procedimientos médicos endoscópicos en caninos en la “Clínica Veterinaria UEB” . - Gaibor Naranjo, Andrea Estefanía (2022)
In the present investigation, Determination of alterations of the upper digestive system by means of endoscopic medical procedures in canines at the Veterinary Clinic UEB, whose objectives were: To examine the pathological alterations of the upper digestive system of canine patients during the investigation, to create a protocol on the methodology correct for the diagnosis of the different alterations of the upper digestive system and to determine the indirect collateral effects of endoscopy. Several clinical and cabinet processes were carried out with the evaluation of thirty canine patients who attended a medical consultation and were evaluated by means of a general examination and subsequent endoscopic evaluation. The results obtained were that 66% of canine patients presented some type of digestive alteration, such as acute and chronic gastritis, masses and nodules, esophageal stenosis, and foreign bodies, in addition, the presence of digestive pathologies and their direct relationship with the age, weight, sex, race, diet, body condition as risk factors for the presence of upper digestive disorders that can be diagnosed by endoscopic methods. In this way it was observed that of the pathologies of the upper digestive tract, gastritis of different etiologies has the highest incidence and are the most diagnosed by endoscopic methods.